The Blue Compendium From Knowledge to Action for a Sustainable Ocean Economy - Lubchenco, Jane; Haugan, Peter M. (Springer Nature, 2023)
Home to over 80 percent of all life on Earth, the ocean is the world's largest carbon sink and a key source of food and economic security for billions of people. The relevance of the ocean for humanity's future is undisputed. However, the ocean's great potential to drive economic growth and equitable job creation, sustain healthy ecosystems, and mitigate climate change is not yet fully recognised. Lack of awareness of this potential as well as management and governance challenges pose impediments. Until these impediments are removed, ocean ecosystems will continue to be degraded and opportunities for people lost. A transition and a clear path to a thriving and vibrant relationship between humans and the ocean are urgently needed. This open access collection of papers and reports identifies a path that is inspired by science, energised by engaged people, and emboldened by visionary leaders. These assessments of knowledge are commissioned by the High Level Panel for a Sustainable Ocean Economy (Ocean Panel), which was established in September 2018 as a unique initiative led by heads of state and government from around the world, to showcase the latest leading-edge science, knowledge and state-of-the-art thinking on key ocean issues. Altogether, The Blue Compendium offers innovative ocean solutions in technology, policy, governance, and finance realms, that could help accelerate a transition to a more sustainable and prosperous relationship with the ocean. The comprehensive assessments have already informed policy making at the highest levels of government and motivated an impressive array of responsive and ambitious action across a growing network of leaders in business, finance and civil society.